2019 IEEE/ACM International Conference on Connected Health: Applications, Systems and Engineering Technologies (CHASE) 2019
DOI: 10.1109/chase48038.2019.00024
|View full text |Cite
|
Sign up to set email alerts
|

Fuzzy C-Means Clustering and Sonification of HRV Features

Abstract: Linear and non-linear measures of heart rate variability (HRV) are widely investigated as non-invasive indicators of health. Stress has a profound impact on heart rate, and different meditation techniques have been found to modulate heartbeat rhythm. This paper aims to explore the process of identifying appropriate metrices from HRV analysis for sonification. Sonification is a type of auditory display involving the process of mapping data to acoustic parameters. This work explores the use of auditory display i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…The stimuli featured sequential trials of stressor, guided breathing, and unguided breathing sections ( Figure 1). The stimuli were procedurally generated by Muvik Labs' Augmented Sound™ engine to ensure timing precision and effectiveness through evidence-backed breathing interventions driven by principles of psychoacoustics and behavioral psychology [64].…”
Section: Participants and Data Acquisitionmentioning
confidence: 99%
See 1 more Smart Citation
“…The stimuli featured sequential trials of stressor, guided breathing, and unguided breathing sections ( Figure 1). The stimuli were procedurally generated by Muvik Labs' Augmented Sound™ engine to ensure timing precision and effectiveness through evidence-backed breathing interventions driven by principles of psychoacoustics and behavioral psychology [64].…”
Section: Participants and Data Acquisitionmentioning
confidence: 99%
“…Following an initial EEG baseline recording for 120 sec ('Baseline'), participants performed a 25-min session featuring stress induction and breath modulation tasks consisting of four main blocks. Each block began with a stressor ('Stressor') featuring an augmented arithmetic number task, intensified by bright contrasting colors displaying numbers appearing sequentially, coupled with audible sonified timers mapped to rising pitches similar to Shepard tones (powered by Muvik Labs Augmented Sound™) [64], with a 90 second time constraint. Timed mental arithmetic has been widely used to induce stress [67][68].…”
Section: Stress Induction and Alleviationmentioning
confidence: 99%
“…For example, higher HRV in atrial fibrillation could be heard as a discontinuous jump between high and low pitches with relatively constant tinkling sounds. Further studies investigated the appropriate HRV features to improve the perceptual quality and sonification interpretability [ 23 , 24 , 25 , 26 , 27 ]. An important application was highlighted in aiding the training of athletes who were able to maintain stable target heart rates by using sonification-assisted visual monitoring of HRV [ 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Studies [ 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 ] demonstrated that ECG sonification has the potential to offer real-time monitoring capabilities, enabling individuals to hear irregularities or anomalies in ECG patterns without the need for constant visual attention. Also, humans do not even have to be focused to react to sound (acoustic) alerts.…”
Section: Introductionmentioning
confidence: 99%